Impacto da padronização da fase pré-analítica na avaliação histológica e imuno-histoquímica do câncer de mama - Marcelo Araújo Buzelin (2015)
AIMS: To investigate the influence of preanalytical phase control for assessment of histology and immunohistochemistry (IHC) for estrogen (ER) and progesterone (PR) receptors, HER2 expression and cell proliferation marker Ki67 in samples of invasive mammary carcinomas with the pre-analytical phase controlled, following the ASCO / CAP, with samples of the same tumor with the pre-analytical phase uncontrolled. MATERIALS AND METHODS: 49 invasive mammary carcinomas were prospectively collected from the surgical room of the Hospital das Clinicas, UFMG (HC), between 2011 and 2013, and one tumor sample was immediately sliced and immersed in 10% neutral buffered formalin and fixed for 08-72 hours (Group 1, sample with pre-analytical phase controll). The rest of the specimen was submerged in 10% unbuffered formaldehyde for clinical routine evaluation of the HC service of pathology (Group 2, sample with no pre-analytical phase controll). In 98 of the 49 samples of carcinomas, histological evaluation (presence of autolysis, histological type and grade) and IHC for ER, PR, HER2 and Ki-67 was performed, and interpreted according to current recommendations. RESULTS: Of the 49 initial cases, one had no invasive component of the carcinoma in both groups, and was excluded from the analysis. Evaluations of autolysis and histological type showed statistically significant results. Group 2 had more cases with autolysis (16/48) than Group 1 (6/48). In histological classification there were more cases with specific types in Group 1 (16/48). In Group 2 we identified more cases of ductal pattern (38/48). The evaluation of histological grading and IHC staining for hormone receptors and HER2 showed no significant statistical difference. HER2 expression had varying staining on equivocal and negative cases: more equivocal cases 2+ in Group 1 (5/47) than in Group 2 (2/47) and more negative cases in Group 2, (39/47) than in Group 1 (36/47). One case showed heterogeneous staining, with overexpression 3+ in Group 2 and equivocal 2+ in Group 1. Ki67 assessment did not have significant difference in the mean positivity in both groups; however, when the cut-off level of 20% for Ki67 was compared there was significant difference, with more cases over 20% in Group 2 (21/48) than in group 1 (14/48). CONCLUSIONS: Our study showed statistically significant differences in histological and immunohistochemical results between both groups as autolysis, histological type and ki67 staining parameters. Group 2 had more autolysis and more cases with histological type of ductal pattern. There was no significant difference between groups in the histological grading and immunohistochemical staining for estrogen and progesterone receptors and HER2. IHC evaluation for Ki67 showed more cases considered as high proliferative index (> 20% of cells) in group 2 compared with group 1.